Association between speed and agility abilities with movement patterns quality in team sports players - Kozlenia, D.; Domaradzki, J.; Trojanowska, I.; Czermak, P. (Medicina dello Sport, 2020)
BACKGROUND: Speed and agility are critical abilities in many team sports. Therefore, searching factors that could affect them is relevant. Functional Movement ScreenTM is one of the most used screening tools in movement quality assessment in terms of mobility and stability. It provides observable performance of basic locomotor, manipulative, and stabilizing movements. These abilities are fundamental in movement competency. Hypothetically FMSTM Score should be associated with speed and agility abilities, however possible connection remains unclear. The aim was to investigate association between quality movement patterns with speed and agility abilities in team sports players. METHODS: Thirty-five elite college, male athletes: 13 soccer players 21.34±0.9 years, 11 handball players 21.23±1.2 years, and 11 basketball players 21.37±0.7 years. The FMS test was conducted to determine quality of movement patterns. For speed assessment, the 20-meter sprint test and for agility, the Agility T-test was conducted. RESULTS: There were no significant differences in speed and agility level among the three groups of team sport players. Movement quality differences were noticeable between soccer and handball players. It was found that athletes with lower quality movement patterns (FMS Score =14) achieved poorer times during the speed and agility tests. However, only in Agility T-test, the differences were statistically significant (P<0.05). CONCLUSIONS: Poor quality movement patterns are associated with poorer agility abilities. Shape a good quality movement patterns may have positive effect on agility performance.